Reconstructing the paleoenvironment of Loltún Cave, Yucatán, Mexico, with Pleistocene amphibians and reptiles and their paleobiogeographic implications - José Alberto Cruz; Joaquín Arroyo-Cabrales; Víctor Hugo Reynoso (Revista Mexicana de Ciencias Geológicas)
Loltún cave in Yucatán peninsula is an important fossil site. The cave preserves Pleistocene fauna and lithic tools, and it is among the few sites with amphibian and reptile fossils of the Mexican Pleistocene. We used the fossil amphibians and reptiles community to reconstruct the paleoclimate and paleoenvironment of Loltún cave in the Late Pleistocene. The Pleistocene amphibian and reptiles community in Loltún cave consists of one frog, three lizards, five snakes and one turtle. Applying the Habitat Weighting method to the fossil herpetofaunal assemblage, we inferred a vegetation mosaic non-analog with the present one, comprising evergreen seasonal forest, tropical deciduous forest and scrub forest, in contrast to the tropical semi-deciduous forest found nowadays around Loltún cave. Using the Mutual Climatic Range (MCR) method we inferred a mean annual temperature of 25.33 °C and a mean annual precipitation of 1183.74 mm; the temperature was 1.47 °C lower and the MAP was 85.14 mm higher than the present climate condition. Is the first time that a paleoclimatic reconstruction using amphibians and reptiles in a tropical region is made using the MCR method. Our results are in concordance with other paleoclimatic inferences using fossil pollen as a proxy, extending the use of the MCR method to different climatic regions. We found a range shift of the iguanid Ctenosaura subgenus Loganiosaura during the Late Pleistocene, of 446.4 km north of the present distribution, surely given by the climatic and vegetation structure changes in the past.